Pan Trinbago to Clamp Down on Defiant Steelbands. - Unknown (Newsday)
Pan Trinbago is clamping down on defiant steelbands determined to ignore the rules governing 1999 Panorama. Pan Trinbago stated in a release that the rules which affected the Panorama in 1998 remain in effect. The rules started that players are to perform for only one conventional band and may perform for one single-pan band at the competitions.
Keywords: Steel bands (Music) -- Competitions -- Trinidad and Tobago; Steel bands (Music) -- Administration -- Trinidad and Tobago; Panorama (Musical festival)